S128 CyTOF and in vitro analysis of the role of IL-17A in asthma. (12th November 2019) - Hynes, GM; Downs, TL; Thulborn, ST; Connolly, C; Borg, C; Gittins, A; Shrimanker, R; Moran, A; Brown, MA; Powell, TJ; Morgan, SB; Pavord, ID; et al.
Abstract : Introduction: Many patients with asthma have type-2 low, neutrophilic asthma, and this has been linked to elevated IL-17A levels. We aimed to explore the role of IL-17A in asthma using two approaches: i) mass cytometry by time of flight (CyTOF) profiling of blood and sputum for IL-17A-expressing cells; and ii) in vitro modelling of the effects of IL-17A in epithelial inflammation and the modulatory effects of this produced by major asthma therapies, namely corticosteroids and macrolides. Methods: We collected blood and sputum from patients with well-phenotyped severe asthma. Sputum cells and peripheral blood mononuclear cells were stimulated and stained for intracellular cytokines and extracellular markers using metal-conjugated antibodies. Samples were analysed using the Helios CyTOF 3, and results analysed using FlowJo. We used the bronchial epithelial cell line BEAS-2B to determine whether IL-17A can induce an inflammatory response in epithelial cells, both acting alone and in synergy with different toll-like receptor (TLR) agonists. We investigated Fluticasone and Azithromycin in modulating IL-17A-induced effects. Results: We were able to identify the major IL-17A-expressing cell subsets in severe neutrophilic asthma (figure 1), and showed the predominant source was the distinct CD4+ IL-17A+ (Th17) cell population. By contrast expression of other intracellular cytokines was more widespread across diverse T cell subsets. In vitro modelling demonstrated that IL-17A alone induces the release of IL-8 and IL-6 from BEAS-2B cells at low levels, but in synergy with the different TLR agonists had a pleiotropic effect whereby low concentrations of IL-17A reduced the TLR-induced cytokine expression, while higher concentrations of IL-17A had synergistic effects. Fluticasone and Azithromycin both suppressed epithelial cytokine release. This suppression was independent of IL-17A. Conclusions: We have demonstrated the applicability of CyTOF to samples from respiratory patients and confirmed the predominant IL-17A producing cell-type is CD4+ IL-17A+ T cells in asthma. IL-17A appears to have a pleotropic role in regulating epithelial inflammation with low concentrations providing a suppressive, presumed homeostatic effect on epithelial cytokine release and higher concentrations inducing epithelial release of inflammatory cytokines associated with neutrophilic inflammation. Our data suggests that commonly used treatments for asthma had no effect on this pathway.